Workplace violence and its effect on burnout and turnover attempt among Chinese medical staff. Issue 6 (1st November 2016) - Chen, Shiying; Lin, Shaowei; Ruan, Qishuang; Li, Huangyuan; Wu, Siying
ABSTRACT: The present study was to evaluate workplace violence and examine its effect on job burnout and turnover attempt among medical staff in China. A total of 2, 020 medical employees were selected from Fujian province by using stratified cluster sampling method. The Chinese version of the Workplace Violence Scale and the Maslach Burnout Inventory–General Survey were used to measure the workplace violence and job burnout, respectively. Other potential influencing factors for job burnout and turnover attempt were collected using a structured questionnaire. The incidence of workplace violence among medical staff was 48.0%. Workplace violence had a positive correlation with emotional exhaustion and cynicism and a negative correlation with professional efficacy. Workplace violence, marital status, employment type, working time (≥ 10 h/day), performance recognition, and life satisfaction were significant predictors for turnover attempt among Chinese medical staff.